Paradigms of conflict resolution in South Asia - Ahmar, Moonis (Dhaka : University Press Ltd., 2003)
Contributed workshop articles.
Mutahir Ahmed -- India and its northern and eastern neighbours : confidence-building through cooperation / Smruti S. Pattanaik -- India-Pakistan summit diplomacy : lessons learned / Karan R. Sawhny and Nidhi Narain -- Sri Lanka peace prospects / Sugeeswara Senadhira -- Vision of South Asia in 2047? : perceptions on conflict resolution / Nabiha Gul, Maria Saifuddin and Nadia Khalil -- The vision of South Asia in the year 2047? : perceptions on cooperative security / Nausheen Wasi -- Vision of South Asia in the year 2047? : perceptions on human development / Naeem Ahned.
Includes bibliographical references and index.
Refugee Studies Unit (RSU), CPJ
Keywords: Conflict management -- South Asia -- Congresses